2006
DOI: 10.1086/507831
|View full text |Cite
|
Sign up to set email alerts
|

HSTNICMOS Imaging of the Planetary‐mass Companion to the Young Brown Dwarf 2MASSW J1207334−393254

Abstract: Multiband (0.9Y1.6 m) images of the TW Hydrae association (TWA) brown dwarf 2MASSW J1207334À 393254 (also known as 2M 1207) and its candidate planetary-mass companion (2M 1207b) were obtained on 2004 August 28 and 2005 April 26 with HST NICMOS. The images from these two epochs unequivocally confirm the two objects as a common proper motion pair (16.0 confidence). A new measurement of the proper motion of 2M 1207 implies a distance to the system of 59 AE 7 pc and a projected separation of 46 AE 5 AU. The NICMOS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 25 publications
3
60
0
Order By: Relevance
“…By contrast, the frequency of hot Jupiters around M-stars is lower than that for higher mass stars (e.g., Johnson et al 2010). The detection of brown dwarfs with directly-imaged planetary mass companions (Chauvin et al 2004;Song et al 2006) indicate that at least some substellar objects are associated with planet formation early in their history. The overall exoplanet population frequency remains unclear around brown dwarfs.…”
Section: Introductionmentioning
confidence: 90%
“…By contrast, the frequency of hot Jupiters around M-stars is lower than that for higher mass stars (e.g., Johnson et al 2010). The detection of brown dwarfs with directly-imaged planetary mass companions (Chauvin et al 2004;Song et al 2006) indicate that at least some substellar objects are associated with planet formation early in their history. The overall exoplanet population frequency remains unclear around brown dwarfs.…”
Section: Introductionmentioning
confidence: 90%
“…More recently, Mamajek (2005) has discussed the membership of TWA22 AB to TWA based on its kinematics properties and estimates a probability of 2% for TWA22 to be a member of TWA from an implemented convergence point technique (de Bruijne 1999). However, Song et al (2006) mentioned that the strong Li line of TWA22 AB is observed only for young active M dwarfs in the direction of TWA with the exception of a very few M-type members of the β Pictoris moving group (BPMG). Finally, Mentuch et al (2008) obtained a new visible high-resolution spectrum of TWA22 AB.…”
Section: Age and Membership Of Twa22 Abmentioning
confidence: 99%
“…By converting the K s absolute magnitude into luminosity using a bolometric correction appropriate for mid and late-L dwarfs (Golimowski et al 2004), based on his nearer distance estimate, he derived a mass of 3-4 M Jup from both DUSTY and COND evolutionary models (Baraffe et al 2003). With HST/NICMOS multi-band (0.9 to 1.6 µm) photometry and a distance estimate of 59±7 pc, Song et al (2006) derived a mass of 5 ±3 M Jup for 2M1207 b, due to its brighter flux than expected from model predictions at shorter wavelengths (for a given mass and age) and to the scatter in the emergent flux predicted by the DUSTY and COND03 evolutionary models at wavelengths less than 2.2 µm (and shown in Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…The space motion determination for the TWA was based on the four members with known Hipparcos distance: TWA1, TWA4, TWA9, and TWA11. Song et al (2006) suggests that significant uncertainties in the Hipparcos distance to TWA9 might affect the cluster distance estimation. They proposed a new distance estimate of 59 ± 7 pc based on an improved proper motion determination for 2M1207A scaled with the proper motion and the Hipparcos distance to HR 4796 A (TWA11).…”
Section: Introductionmentioning
confidence: 99%